2015
DOI: 10.15621/ijphy/2015/v2i5/78229
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Exercises During Antenatal and Postnatal

Abstract: Background: It's a well-known fact that exercise is good for the mind and body making it beneficial for expectant and new mothers. The challenge of pregnancy, labor and looking after a new born is not an easy task. So the fitter you are the better you will cope with this life changing event.Method: Aerobic and strengthening exercises help in adjusting to the increasing weight and posture changes to cope effectively with the labor and the postnatal period. Although exercises in pregnancy are extremely beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…It has been documented those conservative measures like physiotherapy[ 25 ] can easily prevent and even cure many fitness-related problems of antenatal and postnatal women which are found in the present study also. It was found that prenatal and postnatal women’s capacity for standing, walking, and sitting diminished.…”
Section: Discussionsupporting
confidence: 72%
“…It has been documented those conservative measures like physiotherapy[ 25 ] can easily prevent and even cure many fitness-related problems of antenatal and postnatal women which are found in the present study also. It was found that prenatal and postnatal women’s capacity for standing, walking, and sitting diminished.…”
Section: Discussionsupporting
confidence: 72%